2014
DOI: 10.1039/c4ob00935e
|View full text |Cite
|
Sign up to set email alerts
|

A new class of high-contrast Fe(ii) selective fluorescent probes based on spirocyclized scaffolds for visualization of intracellular labile iron delivered by transferrin

Abstract: Iron is an essential metal nutrient that plays physiologically and pathologically important roles in biological systems. However, studies on the trafficking, storage, and functions of iron itself in living samples have remained challenging due to the lack of efficient methods for monitoring labile intracellular iron. Herein, we report a new class of Fe(2+)-selective fluorescent probes based on the spirocyclization of hydroxymethylrhodamine and hydroxymethylrhodol scaffolds controlled by using our recently esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 70 publications
3
75
0
1
Order By: Relevance
“…RhoNox‐1 interacts with Fe 2+ resulting in the release of fluorescent rhodamine and was recently reported to selectively detect endogenous changes in LIP of lung carcinoma cells (Niwa et al . ; Adachi et al . ), while IP‐1 relies on an oxygen‐dependent, three‐component sensing mechanism to detect Fe 2+ (Au‐Yeung et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoNox‐1 interacts with Fe 2+ resulting in the release of fluorescent rhodamine and was recently reported to selectively detect endogenous changes in LIP of lung carcinoma cells (Niwa et al . ; Adachi et al . ), while IP‐1 relies on an oxygen‐dependent, three‐component sensing mechanism to detect Fe 2+ (Au‐Yeung et al .…”
Section: Resultsmentioning
confidence: 99%
“…Background fluorescence was subtracted and data were expressed as mean +/À SD from 6 replicates. Fe 2+ -specific probes Rho-Nox1 and IP-1 were prepared by Allegra Aron, Ho Yu Au-Yeung and Christopher J. Chang (Department of Chemistry, University of California, Berkeley) and freshly dissolved in dimethylsulfoxide at a stock concentration of 2 mmol (Au-Yeung et al 2013;Niwa et al 2014). Cells were incubated with DMEM media alone or increasing Mn doses for 24 h, washed with PBS and loaded with 5 lmol RhoNox-1 dissolved in OptiMEM media for 60 min.…”
Section: Quantification Of the Labile Iron Pool (Lip)mentioning
confidence: 99%
“…2B). Because increased DMT1 expression potentially leads to elevated iron uptake, we next determined Fe 2+ uptake using RhoNox-1, a fluorescent probe that specifically recognizes Fe 2+ (34,41). We showed that duodena treated with FeSO 4 showed a stronger signal in IECs by RhoNox-1 staining (Supplemental Fig.…”
Section: Dmt1 Mrna Expression and Iron Uptake Are Increased In Diabetmentioning
confidence: 99%
“…RhoNox-1, a fluorescent probe that specifically binds Fe 2+ (34), was purchased from Goryo Chemical (Sapporo, Japan). Rabbit anti-HIF2a (NB100) and mouse anti-human DMT1 (H00004891) antibodies were purchased from Novus Biologicals (Littleton, CO, USA).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…In this regard, detection of iron with both metal and oxidation state specificity is of central importance, because while iron is stored primarily in the ferric oxidation state, a ferrous iron pool loosely bound to cellular ligands, defined as the labile iron pool (LIP), exists at the center of highly regulated networks that control iron acquisition, trafficking, and excretion. Indeed, as a weak binder on the Irving-Williams stability series (13), Fe 2+ provides a challenge for detection by traditional recognition-based approaches (14), and as such we (15)(16)(17) and others (18)(19)(20) have pursued activity-based sensing approaches to detect labile Fe 2+ stores in cells (21)(22)(23)(24)(25). These tools have already provided insights into iron biology, as illustrated by the direct identification of elevations in LIPs during ferroptosis (26,27), an emerging form of cell death, using the ratiometric iron indicator FIP-1 (15).…”
mentioning
confidence: 99%